Construction of a composite cooling network for the mitigation of urban heat risk in Fuzhou - Xu, Haozhe; Yang, Jianfeng; Lin, Yan; Xu, Nuo; Li, Mingzhe; Xu, Yan; Liu, Xingzhao; Li, Fangying (Frontiers in Environmental Science, 2024)
Climate change has intensified urban heat risks through extreme heat and heat island effects. Using Fuzhou as a case study, we conducted assessments of heat risk and cool island quality to identify core heat risk sources (CHRSs) and core cold sources (CCSs). Based on the degree of resistance to surface heat transfer, we constructed a comprehensive resistance surface. This was followed by the construction of a composite cooling network using the minimal cumulative resistance and circuit theory models, along with the identification of key nodes to enhance the protection of cool island resources and ensure network stability. Our findings revealed that the central urban area had the highest heat risk, followed by the eastern coastal areas, showing a trend of further expansion towards the southeastern coast. Relatively high-quality cool island resources were distributed in the western mountainous area. We identified 21 CHRSs and 32 CCSs. The composite cooling network included 94 heat transport corridors and 96 cool island synergy corridors, with 148 cooling nodes and 78 barrier nodes. The average land surface temperature of transport and synergy corridors was 27.89°C and 25.34°C, respectively, significantly lower than the high-risk areas (31.14°C). Transport corridors enable heat transfer from CHRSs to CCSs, while synergy corridors can achieve further cooling by enhancing the synergy among cool islands.